2022
DOI: 10.1002/ejoc.202200775
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroisocyanuric Acid (TCCA): A Suitable Reagent for the Synthesis of Selanyl‐benzo[b]chalcogenophenes

Abstract: A new approach for the synthesis of 3‐organoselanyl‐benzo[b]chalcogenophenes promoted by trichloroisocyanuric acid is reported. The reaction was carried out with electrophilic selenium species which were generated in situ by the reaction between trichloroisocyanuric acid and diorganyl diselenides using ethanol as solvent. The developed method uses mild reaction conditions and was efficient for the synthesis of different 3‐organoselanyl‐benzo[b]chalcogenophenes in a good to excellent yields. Analysis of 77Se NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Based on the literature 13 and the data collected from a set of control experiments that are described in the supplementary material, we suggest a plausible mechanism as depicted in Scheme 4. We assume that the reaction between diselenide 2 and TCCA occurs previous to any interaction with enaminone 1 , in order to generate electrophilic selenium species I and/or II , or maybe both.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Based on the literature 13 and the data collected from a set of control experiments that are described in the supplementary material, we suggest a plausible mechanism as depicted in Scheme 4. We assume that the reaction between diselenide 2 and TCCA occurs previous to any interaction with enaminone 1 , in order to generate electrophilic selenium species I and/or II , or maybe both.…”
mentioning
confidence: 91%
“…Recently, some research groups have demonstrated the generation of electrophilic selenium species from diorganoyl diselenides, through the use of the cheap and non-toxic chlorinating agent trichloroisocyanuric acid (TCCA), under mild conditions. 13…”
mentioning
confidence: 99%
“…The compounds 3-selanyl benzo[ b ]furans (SeBZF 1–5 ) (Figure ), named 2-phenyl-3-(phenylselanyl)benzofuran (SeBZF 1 ), 3-((4-fluorophenyl)selanyl)-2-phenylbenzofuran (SeBZF 2 ), 3-((4-methoxyphenyl) selanyl)-2-phenylbenzofuran (SeBZF 3 ), 3-((4-chlorophenyl)selanyl)-2-phenylbenzofuran (SeBZF 4 ), and 2-phenyl-3-(4-tolylselanyl)benzofuran (SeBZF 5 ), were synthesized and characterized in the Laboratory of Synthesis of Selenium and Tellurium Derivatives (LabSelen) located at the Federal University of Santa Catarina (UFSC) employing the method previously described by Blödorn et al 1-Methoxy-2-(phenylethynyl)benzene (1.0 mmol), corresponding diaryl diselenide (0.55 mmol), EtOH (1.5 mL), and TCCA (0.33 equiv = 0.060 g) were added to a 10.0 mL reaction balloon. Then, the reaction mixture was allowed to react at room temperature for 1 h. After completion of the reaction, the mixture was extracted with ethyl acetate and washed with water, dried over MgSO 4 , and concentrated under vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…The data that support the findings of this study are available in the supplementary materials of this article. Additional references cited within the Supporting Information [24–26] …”
Section: Supporting Informationmentioning
confidence: 99%
“…In 2019, Perin and Lenardão reported a synthesis of 2,3‐bis‐selenylated benzothiophenes using electrophilic selenium species generated in situ by the reaction of Oxone and diselenides under the reflux conditions in ethanol (Scheme 1, A1) [10,11] . Recently, Neto and Alves developed a synthesis for 3‐selanyl benzothiophenes promoted by trichloroisocyanuric acid (TCCA) [12] . The reactions were performed with in situ generated electrophilic selenium species formed from diselenides and TCCA.…”
Section: Introductionmentioning
confidence: 99%